PENGARUH BERMAIN FANTASI DI LUAR KELAS TERHADAP KEMAMPUAN FISIK MOTORIK ANAK PADA TK SIPURIO SIPURENNU KECAMATAN AWANGPONE KABUPATEN BONE - Iting, Andi (Institut Agama Islam Negeri Bone, 2020)
This Research discusses the The Influence Of Gymnastics Fantasy Towards Phsycal Motor Skills Of Children At TK Sipurio Sipurennu In Awangpone Bone District. The purpose of this study is to the implementation of gymnastics fantasy, (ii) the physical motor skills of children before (pretest) an after (posttest) conducted gymnastics fantasy, and (iii) the influence of gymnastics fantasy toward physical motor of children. To obtain the data in this study researchers used a quanitative research method, with pre-eksperimen. Data’s collection techniques in this research is observation, interview, and documentation. Based on the results of research conducted in in kindergarten grace the District Awangpone Bone regency it could be concluded that the implementation of gymnastics fantasy consisted three components, namely warning-up activity, core activity, and cooling-down activity, the physical motor skills of children before conducted gymnastics fantasy was in low category and it was in high category after the gymnastics fantasy was conducted, and there were positive influences of gymnastics fantasy toward physical motor of children at At TK Sipurio Sipurennu In Awangpone Bone District. Keywords: Fantasy Gymnastics; Physical Motor Children